Actualization of Islamic Education Curriculum Values from the Perspective of the Philosophy of Science in the Era of Artificial Intelligence (A Study at SMPN 4 Banjar City) - Fadloli, Muhamad; Zulkarnaen, Nurwahid; Haq, Ahmad Munadhil Izzul; Hamdani, Djaswidi Al; Rizal, Soni Samsu (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
The development of Artificial Intelligence (AI) presents both challenges and strategic opportunities for the field of education, including the strengthening of the Islamic Education Curriculum. This study aims to analyze the actualization of Islamic Education curriculum values from the perspective of the philosophy of science in the era of artificial intelligence, based on an empirical study conducted at SMPN 4 Banjar City. The focus of the analysis is directed toward how the ontological, epistemological, and axiological values of Islamic Education are internalized and adapted within learning practices that increasingly engage with AI-based technologies. This research employs a qualitative approach using a case study method, with data collected through in-depth interviews, participatory observation, and analysis of curriculum documents and instructional practices. The findings indicate that the actualization of Islamic Education curriculum values positions students not only as learners who are faithful and morally grounded, but also as rational and critical agents capable of utilizing AI technology in an ethical and responsible manner. From the perspective of the philosophy of science, the ontological dimension is reflected in the reinforcement of the understanding of human nature as rational and moral beings; the epistemological dimension is evident in the integration of sources of knowledge derived from revelation, reason, and technology; while the axiological dimension is manifested in value orientations toward public benefit (maslahah), justice, and social responsibility. This study affirms that Islamic Education in the era of artificial intelligence should not adopt a resistant stance toward technology, but rather undertake a reflective and critical reconstruction of values in order to remain relevant, humanistic, and transformative in shaping students’ character amid digital disruption.